THE MEANING AND LIVED EXPERIENCE OF DEPLOYMENT AS PERCEIVED BY MILITARY OFFICERS' SPOUSES/PARTNERS - Bitner, Marcy Matson (East Carolina University, 2011)
This study addressed the question, "What is the lived experience of and meaning held by military officers' spouses/partners regarding multiple, year-long or longer deployments of their active duty military wife/partner in the post-9/11 era?" A literature review indicated a paucity of information about this relatively new phenomenon and that the impact on spouses/partners warranted investigation. Study findings provide insight for health professionals about the stressors experienced and coping mechanisms utilized by military officer spouses/partners during repeated yearlong or longer deployment. The findings afford an in-depth understanding of the complex and emerging issues faced by these individuals.  The researcher used Max van Manen's approach to hermeneutic phenomenology to guide the study. This approach focused on employing individuals' reflections on their experiences to reach an understanding of the deeper meaning of the experience. The essence of the experience was ambiguous loss and resilience. The researcher used purposive sampling to recruit seven participants who were spouses of military officer spouses for five and seventeen years and who experienced between two and six spousal/partner deployments. Strategies to address study credibility included methodological congruence, triangulation, thick description, prolonged engagement in the field, continuing search for disconfirming evidence, verbatim transcription, engagement in reflexivity, maintenance of an audit trail, and data saturation. Data were coded and analyzed for patterns and themes in an effort to identify the essence of participants' lived experience.
Keywords: Health education; Public health; Social research; Ambiguous loss; Military deployments; Military families; Qualitative; Stressors; Stress (Psychology); Life skills; Military spouses--United States; Officers' spouses--United States